Metric and non-metric guides for the determination between fore- and hindlimb phalanges of Rangifer tarandus - Hull, Emily H (Rangifer, 2019)
Phalanges are a great untapped resource in the zooarchaeology of Rangifer tarandus. The utilization of this resource, however, is constrained by a current inability to consistently differentiate fore- from hindlimb phalanges in a mixed assemblage. The ability to separate and identify forelimb and hindlimb phalanx 1 (PI) and phalanx 2 (PII), as well as to recognize and identify other small bones of the hoof, leads to great opportunities for archaeologists. In large scale-analysis, this capacity allows a greater ability to determine minimum number of individuals and assess butchery and transport practices. In the examination of individual life histories of Rangifer tarandus, these designations allow a more precise study of pathology and entheseal change, which can shed light on adaptation, foraging strategy, and human-animal interactions. This study presents qualitative and quantitative methods for the differentiation of PI and PII of the fore- and hindlimbs and describes other bones of the hoof. Metric techniques were developed to differentiate fore- from hindlimb phalanges using non-invasive, non-destructive, and simple methods. The efficacy and accuracy of these methods were assessed using blind testing by students and staff. The average success rates of metric analysis yielded 87% accuracy for determinations of fore- versus hindlimb PI and 92% accuracy for determination of fore- versus hindlimb PII. These results show that this method could benefit researchers working with Rangifer tarandus remains.